Case of Spontaneously Reported Hypersensitivy in the Ultra-Early Phase of Normal Tension Glaucoma in a Japanese Man - Fujimoto, Hisataka; Kiryu, Junichi (Journal of Ophthalmology and Research, 2022)
Background: We report a case of spontaneous reported hypersensitivity in ultra-early phase in normal tension glaucoma in a Japanese professor in a medical school. Case Presentation: At 66 years of age, the patient spontaneously noticed subjective symptoms, such as scotoma, in the visual field in the temporal lower position in the right eye while he examined his electronic microscopy (EM) study images. A slit lamp examination during the first visit to our hospital revealed a typical localized glaucomatous retinal nerve fiber layer defect in red-free filter examination and glaucomatous optic nerve head damage with 0.8 of cup-to-disc ratio and rim thinning and excavation. Moreover, optical coherence tomography examination of his optic nerve and macula (ILM-IPL/INL) revealed thinning of the retinal ganglion cell layer, especially in the right eye in which he had noticed the symptom. Furthermore, Humphrey automated perimetry was performed on the same day, confirming scotoma in the right eye coinciding with his spontaneous subjective symptom. Conclusion and Importance: Glaucoma is normally asymptomatic and medical treatment is often delayed owing to the lack of subjective symptoms in the early phase. However, in this case, the patient’s careful and sensitive personality enabled spontaneous subjective identification in the ultra-early phase of normal tension glaucoma.